Simple rules on adjectival endings in zoological nomenclature and their use in scale insect names (Hemiptera: Sternorrhyncha: Coccoidea), with some corrections to combinations in common use - Pellizzari, Giuseppina; Williams, Douglas J. (Zootaxa, 2013)
We give some simple rules on Latin grammar to help scale insect systematists to apply the correct adjectival gender endings to species names. We list some common errors that have occurred when species names have either been proposed with a wrong gender ending or when they have been transferred from one genus to another. We also correct the gender endings to several species names in a few families.